Effects of TLR7 Polymorphisms on the Susceptibility and Progression of HIV-1 Infection in Chinese MSM Population - Zhang T; Zhu JP; Su B; Cao LN; Li Z; Wei HH; Huang XJ; Zheng K; Li AX; Chen N; Liu LF; Xia W; et al. (Frontiers Research Foundation, 2022)
Toll-like receptor (TLR) 7 plays a key role in innate and adaptive immunity for HIV-1 infection. We evaluated the effect of TLR7 polymorphisms on disease susceptibility and progression of HIV-1 infection in Chinese MSM (men who have sex with men). Blood samples were taken from 270 patients with laboratory confirmed HIV infection, 196 male controls were tested, and three TLR7 intronic polymorphisms (rs179010-C > T, X:12884766; rs2074109-T > C, X:12885330; and rs179009-A > G, X:12885361) were analyzed by PCR-based sequencing. The frequency of TLR7 rs179010 T allele was significantly lower in MSM patients than in controls (P = 0.039). The haplotype TTA was associated with a decreased susceptibility to HIV-1 infection (P = 0.013), especially to acute HIV-1 infection (AHI) (P = 0.002), but not to chronic HIV-1 infection (CHI). Furthermore, the haplotype TTA is linked to slow disease progression in AHI patients (P = 0.002) and a lower viral load (P = 0.042). In contrast, TLR7 rs179009 allele A contributed to a higher set point in AHI patients with rapid progression, and the frequency of rs179009 minor allele G was over-presented in CHI patients. This finding supports a role for genetic variations of TLR7 in susceptibility and disease progression of an HIV-1 infection in Chinese Han population and warrants further studies on the effect of TLR7 polymorphisms on HIV-1 infection in different populations.